Fracture response of mitred X70 pipeline with crack defect in butt weld: Experimental and numerical investigation. (August 2022) - Jiang, Jinxu; Zhang, Hong; Zhang, Dong; Ji, Beilei; Wu, Kai; Chen, Pengchao; Sha, Shengyi; Liu, Xiaoben
Abstract: Crack defects in mitred bends seriously affect the structural safety of steel pipelines. Therefore, particular attention should be paid to fracture failure of mitred bends due to stress concentration and formation of defects. In this paper, the fracture response of mitred butt girth weld pipeline with crack defect was investigated by conducting full-scale experiments on failure pressure of mitred bend with crack in girth weld. The experimental results estimated the failure pressure of cracked mitred pipes with different mitre angles of 0° and 5° to 11.85 MPa and 11.38 MPa, respectively. At constant mitre angle, circumferential burst failure appeared for defect-free mitred bend, while longitudinal leakage failure occurred on cracked mitred pipe. A refined finite element model of mitre pipe with crack defect was then established based on the experimental results. Also, parametric numerical simulation analyses were carried out to study the effects of defect location, soil spring stiffness, as well as geometric parameters of pipes and crack like mitre angle, mitre length, pipe diameter, wall thickness, crack length, and crack depth on crack driving force of mitred bend. The data revealed unsafe service of mitred pipe for defects located on the internal angle and outer wall of mitred pipe. The crack driving force increased with the increment in mitre angle, wall thickness, crack length, and crack depth. A negative correlation was observed between crack driving force and other factors, such as mitre length and soil spring stiffness. Based on the 6800 numerical results derived from parametric numerical model realized by python and ABAQUS, a hybrid prediction model employing support vector regression (SVR) and particle swarm optimization (PSO) was established to predict the pipe's crack driving force at the weld. A relative error of 13.3% was obtained between the numerical and established driven model results. In sum, the proposed method looks useful for integrity assessment of mitred X70 pipes. It can also be referenced for fitness for service assessment of energy pipes. Finally, some suggestions about maximum allowable mitre angle for mitred bends with various mitre lengths are given. Highlights: Full-scale experiments on failure pressure of mitred bend with crack defect is conducted. A rigorous FE model for fracture response analysis of mitred X70 pipeline with crack defect in butt weld is proposed. Effects of defect location, soil spring stiffness, geometric parameters of pipes and crack on crack driving force of mitred bend are investigated. A hybrid prediction model employing support vector regression (SVR) and particle swarm optimization (PSO) with relative error of 13.3% is established.